Effectivness on the Use of IPA Funds in Albania Covering the Period 2014-2016 - Kepi, Jola (Himci) (European Scientific Journal, ESJ, 2018)
The utilization of foreign aid and especially EU funding in Albania has been of high interest by both the Government and Developing Partners on their use, transparency and accountability on mobilization on effective use of development resources in the country. This paper intends to provide an analytical overview of development partners’ activities in Albania especially the European Union covering the period 2014-2016, mapping of their support in a variety of sectors, as well as the impact of their support in line with country priorities and the achievement of country’s objectives toward the European Integration. First we look at the effectiveness of external aid as a whole in different sectors and make an analyses of the contribution per donors and especially EU and secondly, we analyze the fact of the EU contribution is it good and enough source to stimulate economic growth in Albania in line with the European Agenda. The finding shows that financial resources are not fully absorbed by the country and there is a need to establish and strengthening the Integrated Policy Management Group (IPMG) per each sector as e mean to monitor, influence and recommend areas of intervention in order to increase the effectiveness and the external use of the financial resources available.